Aspectos fenológicos, locacionais e sociais na arborização em via pública - Croce, Ciro Guilherme Gentil [UNESP]; Guerrini, Iraê Amaral [UNESP]; Bueno, Osmar de Carvalho [UNESP] (My University, 2012)
The project “Phenological, physical and social aspects of afforestation and urbanization on public street” proposes a model of adaptation to urban areas in the choice of species, substrate, implantation sites and local community participation. It was implemented at Dr. Vital Brasil Avenue, in the Botucatu city, São Paulo, Brazil. There were used the species Jacaranda mimosifolia, on the median of the boulevard and Tibouchina mutabilis at the sidewalk. The project was divided into three parts that complemented each other in the process of planning and choice of species with the locacional aspects of the survey, the involvement of local residents for acceptance and preservation of the planting and use of urban and industrial wastes as substrates for the seedlings planted. As a result, it had a satisfactory community approval, the locacional of the seedlings will bring comfort to the environment and the substrate waste has been used as efficient as conventional ones used previously.

O projeto de pesquisa “Aspectos fenológicos, locacionais e sociais na arborização urbana em via pública” propõe um modelo de adequação à arborização urbana na escolha de espécies, substratos, locais de implantação e participação da comunidade local. Foi implantado na Avenida Dr. Vital Brasil, na cidade de Botucatu, SP como modelo para a cidade. Foi utilizada a espécie Jacaranda mimosaefolia, no canteiro central da avenida, e a Tibouchina mutabilis nas calçadas. O projeto foi dividido em três partes que se complementaram no processo de planejamento e escolha das espécies com o levantamento dos aspectos locacionais, o envolvimento dos moradores locais para aceitação e preservação do plantio e utilização de resíduos urbanos e industriais como substratos para as mudas implantadas. Como resultado teve-se uma aprovação da comunidade satisfatória, a localização das mudas trará maior conforto para o ambiente e o substrato de resíduos utilizado foi tão eficiente quanto os convencionais utilizados anteriormente. Palavras-chave: arborização urbana, Jacaranda mimosaefolia, Tibouchina mutabilis, resíduos urbanos e industriais.
Phenologycal, locational and social aspects of trees in public streets
Keywords: Urban afforestation; Jacaranda mimosaefolia; Tibouchina mutabilis; Municipal and industrial waste; Arborização urbana; Jacaranda mimosaefolia; Tibouchina mutabilis; Resíduos urbanos e industriais